DINAMIKA KORUPSI DALAM SISTEM BIROKRASI: STRATEGI SOLUTIF DAN IMPLEMENTASI KEBIJAKAN EFEKTIF - Muhaimin, Hikmah; Utama, Jenny Yudha; Afandi, Ahmad Hasan; Alifa, Nur; Rosana, Nunik (LPPM UNAIM, 2025)
Bureaucracy plays an important role in Indonesian government and society, corruption in the public sector is one of the biggest challenges that hinders efforts to create a clean bureaucracy with integrity in Indonesia. The strategy in creating effective policies and eradicating corruption is to integrate preventive, repressive and collaborative approaches. The preventive approach involves anti-corruption education, strengthening integrity values, and increasing transparency in bureaucratic processes through the use of digital technology, such as e-government and online-based information systems. The repressive approach includes firm and non-discriminatory law enforcement, imposing heavy sanctions on perpetrators of corruption, as well as strengthening internal and external supervisory institutions. This article discusses solution and effective strategies that can be implemented to overcome corruption in the public sector with the aim of creating a clean and transparent bureaucracy.